Parental Altruism and Inter Vivos Transfers: Theory and Evidence - Altonji, Joseph G.; Hayashi, Fumio; Kotlikoff, Laurence J. (Journal of Political Economy, 1997)
This paper uses Panel Study of Income Dynamics data on the extended family to test whether inter vivos transfers from parents to children are motivated by altruism. Specifically, the paper tests whether an increase by one dollar in the income of parents actively making transfers to a child coupled with a one-dollar reduction in that child's income results in a one-dollar increase in the parents' transfer to the child. The authors find that redistributing one dollar from a recipient child to donor parents leads to less than a thirteen-cent increase in the transfer–far less than the one-dollar increase implied by altruism. Copyright 1997 by the University of Chicago.